New generation sequencing in diagnosis of congenital anemias - Canatan, Duran; Altunsoy, Emel; Bauer, Peter (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Congenital anemias are a wide spectrum of diseases including hypoproliferative anemia syndromes, dyserythropoietic anemias, sideroblastic anemias, red blood cell membrane and enzymatic defects, hemoglobinopathies, and thalassemia syndromes. Next-generation sequencing approach including targeted panel, whole-exome sequencing (WES) and Whole Genome Sequencing (WGS) have become more accessible as a diagnostic tool, and played an important role in more undiagnosed cases. In this study, we aimed to present NGS results of patients with congenital anemia who were admitted to our center and to discuss in literature studies. Material and methods: A total 11 patients (8 female, 3 male) the distribution of age was 1-25 years and mean±SD: 8.54±16.9 years. Bone marrow/anemia panel was applied to seven cases; WES was applied to three cases and WGS was applied to one case. Results: Eleven patients have been diagnosed with a definite diagnosis as followed up; autosomal dominant spherocytosis type-1in two patients, autosomal dominant spherocytosis type -2 in two patients, autosomal dominant elliptocytosis type 2 in one patient, autosomal recessive pyruvate kinase deficiency plus gamma-glutamyl cysteine synthetase deficiency in one patient, Hb Knosos plus δ0-thalassemia in one patient, diamond blackfan anemia type 1 in two patients, bone marrow insufficiency in one patient and MLASA Syndrome (myopathy lactic acidosis sideroblastic anemia) in one patient. As conclusion, in diagnosis success, patient selection, examination of clinical symptoms and medical records, and determination of their association with the possible genetic variations and mutations detected by WES/WGS, and close cooperation between clinician and genetic evaluation centre are crucial.